Analysis Of Financial Management Accounting Practices In The Tourism Start – Up Of Sumberaji Village - Ellyana Endang Dewi Pratiwi; Yuniep Mujati Suaidah (Proceeding International Conference on Digital Education and Social Science, 2025)
This study aims to analyze accounting practices in the financial management of tourism in the village of Sumberaji, Slaji Hamlet, Kabuh Subdistrict, Jombang Regency. The study uses a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. Informants consisted of the village head, BUMDes administrators, treasurers, and community members. The results show that tourism financial management has covered the stages of planning, recording, fund management, reporting, and accountability in accordance with village regulations. However, accounting practices are still carried out in a simple and manual manner, with limited human resource competencies and the absence of an application-based recording system. Transparency and accountability have been pursued through village deliberations and information boards, but have not been carried out optimally and routinely. This study concludes that there is a need to improve the capacity of managers and the accounting system to support more transparent and sustainable village tourism financial management.